Urbanization in Nepal: Focus on Pre-requisites and Trend (Journal of Population and Development, 2022)
This study aims at assessing the basic pre-requisites and trends of urbanization in Nepal. Using secondary sources of data, the study embarks on a successive analysis of the years ranging from 1952 to 2017, while employing a descriptive research design. Simple descriptive tools: tabulation, percentage, and trend line are used for data presentation and analysis. Urbanization in Nepal is defined as a crucial way in terms of the rise in the proportion of the total population residing in designated urban areas; not by the sufficient availability of infrastructures but by the excessive migration of people from rural to urban areas seeking modern amenities. The official statistics show that the trend of urbanization in Nepal is in increasing order in recent years. This is the by-product of ad-hoc political decisions. However, this paper limited its scope by considering only pre-requisites, and trends as a measure to examine the pattern of urbanization in Nepal. This paper provides insightful guidelines, and problems solving strategy, especially, for decisionmakers, policy makers, planners, demographers and academicians in relation to developing countries. Academic integrity, professional ethics, and minimum similarity index are used.